2019
DOI: 10.1016/j.conbuildmat.2019.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the polymer structure of polycarboxylate-based superplasticizers on the intercalation behaviour in montmorillonite clays

Abstract: The influence of polymeric structure of polycarboxylate-ether (PCE) based superplasticizers on the intercalation behavior in sodium montmorillonite clay (Na-MNT) is investigated by performing in-situ X-ray diffraction (XRPD) on fresh, unaltered clay pastes. The use of this technique reveals the real influence of the PCE structure and of the PCE/clay dosage ratio on the expansion profile of the clay. This is not observed with the traditional XRPD methodology performed on dried clay pastes, which shows the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…The understanding of the intercalation mechanism has been complemented thanks to the measurements of interlayer d-spacing using in situ XRPD analysis on fresh, unaltered clay pastes [17]. Using this methodology, it is demonstrated that the expansion of MNT clays produced by the intercalation of PCE side chains is larger than that deduced from the aforementioned studies and revels the true influence of the structure of PCE polymers in the affinity for intercalating inside montmorillonite clays, as presented by the authors in [18]. None of these observations can be clearly identified by the typical analytical method used to measure the interlayer d-spacing, which is based on XRPD analysis performed on centrifuged and dried clay pastes [17].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The understanding of the intercalation mechanism has been complemented thanks to the measurements of interlayer d-spacing using in situ XRPD analysis on fresh, unaltered clay pastes [17]. Using this methodology, it is demonstrated that the expansion of MNT clays produced by the intercalation of PCE side chains is larger than that deduced from the aforementioned studies and revels the true influence of the structure of PCE polymers in the affinity for intercalating inside montmorillonite clays, as presented by the authors in [18]. None of these observations can be clearly identified by the typical analytical method used to measure the interlayer d-spacing, which is based on XRPD analysis performed on centrifuged and dried clay pastes [17].…”
Section: Introductionmentioning
confidence: 91%
“…Table 2 presents the characteristics of the PCE and XPE polymers used. The side chain frequency and the side chain density are calculated from the PCE anionic charge, determined by titration with KOH [18].…”
Section: Water-reducer/superplasticizer Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] The clay layers are exfoliated or inflamed (intercalated) in the matrix. [7][8][9][10] Generally, the extent of intercalation/exfoliation depends on the capabilities of polymer chains and clay to interact via interfacial zone. [11][12][13][14] Many researchers tried to use the organically modified clay or compatibilizer to enhance the delamination of clay layers in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, polyethylene glycol might be intercalated preferentially into the interlayer to hinder the intercalation of PCE (Tan et al , 2017). Furthermore, the influence of the polymer structure of PCE (Borralleras et al , 2019b), adsorption conformations (Borralleras et al , 2020) and experimental procedures (Borralleras et al , 2019a) on intercalation behaviour in montmorillonite clays has also been investigated systematically. However, these methods always weakened the side chains of the superplasticizer, which may lead to a loss of dispersing capacity.…”
mentioning
confidence: 99%